2019
DOI: 10.1080/19463014.2019.1628789
|View full text |Cite
|
Sign up to set email alerts
|

Translanguaging by Design in EFL Classrooms

Abstract: This study presents the analysis of a translanguaging by design activity I conducted with students finishing an EFL program at a Costa Rican university, for which I showed them pictures of graffiti in Spanish and encouraged them to discuss these, using their entire linguistic repertoire. I recorded their discussions, selected instances of bilingual languaging, and analyzed their spontaneous and intuitive translanguaging. Whereas classroom interaction showed that students translanguaged for various purposes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This study resonates with the findings of Makalela's investigation (2015b), wherein it is posited that the employment of a translanguaging framework constitutes a efficacious strategy for the reconfiguration of linguistic boundaries (Fallas Escobar, 2019). Students prefer to combine both their L1, and their L2 while studying English, despite what was previously believed.…”
Section: Discussionsupporting
confidence: 86%
“…This study resonates with the findings of Makalela's investigation (2015b), wherein it is posited that the employment of a translanguaging framework constitutes a efficacious strategy for the reconfiguration of linguistic boundaries (Fallas Escobar, 2019). Students prefer to combine both their L1, and their L2 while studying English, despite what was previously believed.…”
Section: Discussionsupporting
confidence: 86%
“…Through this approach, teachers and students can interact well in the classroom. In the learning process, translanguaging can occur naturally or by design (Fallas Escobar, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most studies investigated the practice of translanguaging in EFL classrooms by analyzing classroom interactions. The findings showed that teachers and students employed English, national, and local languages in classroom interactions for various purposes and in clearly distinctive ways (Afriadi & Hamzah, 2021;Fallas Escobar, 2019;Sahib, 2019). Moreover, the effects of implementing translanguaging in EFL classrooms have been discussed.…”
Section: Translanguaging In Efl Classroom Interactionmentioning
confidence: 99%